2010
DOI: 10.1074/jbc.m110.131680
|View full text |Cite
|
Sign up to set email alerts
|

All Mammalian Hedgehog Proteins Interact with Cell Adhesion Molecule, Down-regulated by Oncogenes (CDO) and Brother of CDO (BOC) in a Conserved Manner

Abstract: These results show that all mammalian Hh proteins bind CDO and BOC in the same manner. We also show that interactions between Hh proteins and CDO are weakened at low pH. Formation of Hh-mediated Hh oligomers is thought to be an important feature of normal Hh signaling, but no conserved self-interaction between Hh proteins is apparent from inspection of 14 independent Hh-containing crystal lattices.Hedgehog (Hh) 2 signaling proteins mediate key cell differentiation and tissue patterning events during animal dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…We confirmed that the three critical BDA1 mutations (p.E95K, p.D100E, and p.E131K) were within a negatively charged calcium-binding groove, as shown previously when mapped to the murine SHH structure [28,36]. Furthermore, a recent paper about the complex structure between IhhN and CDOFn 3 has demonstrated that this calcium-binding site is important for the interactions with Ihh partners [30]. The main-chain superimposition between IhhN and its complex with CDOFn 3 gave an RMSD of 0.268 Å, which was mainly contributed by the calcium-binding region.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…We confirmed that the three critical BDA1 mutations (p.E95K, p.D100E, and p.E131K) were within a negatively charged calcium-binding groove, as shown previously when mapped to the murine SHH structure [28,36]. Furthermore, a recent paper about the complex structure between IhhN and CDOFn 3 has demonstrated that this calcium-binding site is important for the interactions with Ihh partners [30]. The main-chain superimposition between IhhN and its complex with CDOFn 3 gave an RMSD of 0.268 Å, which was mainly contributed by the calcium-binding region.…”
Section: Discussionsupporting
confidence: 67%
“…Clearly, p.E95K altered the surface charge within this groove, changing it from negative to positive, without altering the vicinal structure. This alteration could impair the interaction with partner molecules through this groove and would be consistent with impaired PTC1, CDOFn 3 , and HIP1 interactions, as previously demonstrated [27,30], as it would alter the electrostatic interactions that are required. The E95 residue is likely to have an important role in the interaction with partners, as a p.E95G mutation and a specific deletion of this amino acid also leads to a BDA1 phenotype [21,22].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A subfamily of HSPGs, the glypicans, which are anchored to the plasma membrane by a glycosyl-phosphatidyl-inositol (GPI), might contribute to the reception of morphogens such as Hedgehog (Hh) (Gallet, 2011). HSPGs are not alone in this role, as other novel proteins have been implicated, including members of the Ihog/Boi (CDON/BOC) families; Ihog and Boi are essential for Hh signalling in flies Camp et al, 2010;Zheng et al, 2010) and BOC and CDON are essential Shh co-receptors in mammals (McLellan et al, 2008;Kavran et al, 2010;Allen et al, 2011;Izzi et al, 2011). Interestingly, these proteins interact with the extracellular matrix component heparin, which is required for the dimerisation of Ihog and its high-affinity interaction with Hh (McLellan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%